Changing Nigerian Migration Trends and its Hungarian Context - Besenyő, János; Kármán, Marianna (Journal of Central and Eastern European African Studies, 2024)
In a country like Nigeria, there is a decades-long tradition of internal and international migration, which has begun to strengthen especially since the country gained its independence. While the postcolonial period - from the 1960s until the 2000s - was marked primarily by the internal migration of workers to administrative and economic centres, with the rise of unemployment in the 2000s, the international migration of the Nigerians also strengthened. As a result of the diverse opportunities offered by international migration, at the 2015 migration summit, Nigerians turned up in relatively large numbers among migrants arriving in Europe via illegal routes. Although Nigerians are essentially leaving their country on legal routes, Nigerian illegal immigrants arriving in 2015-16 have aggravated the situation of Nigerian diaspora and painted a fundamentally negative image of Nigerians. Although most of them returned home, this still did not mean the elimination or alleviation of the problems that still spur migration in Nigeria.